Neutrophil/lymphocyte and monocyte/lymphocyte indexes as predictors of relapse at 1 year after diagnosis of multiple sclerosis in paediatric age - Geria, Maria Leonor Alves de Oliveira (2023)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina